Radar Talks Anne Currie on Cloud Native and Going Green - Currie, Anne (O'Reilly Media, Inc., 2021)
There's no question: climate change is happening. So how is it impacting tech architecture and ops choices today, and what's in store for the future? Brace yourself. In this edition of Radar Talks, longtime tech industry veteran Anne Currie explains how the climate is already affecting tech plans and helps you better understand the changes it's likely to impose on our industry in the next decade. Recorded on September 28, 2021. See the original event page for resources for further learning or watch recordings of other past events.
Online resource; Title from title screen (viewed September 28, 2021)
Keywords: Electronic videos